The Costs of Sovereign Default: Evidence from the Stock Market - Andrade, Sandro C.; Chhaochharia, Vidhi (Review of Financial Studies, 2018)
We use stock market data to test cross-sectional implications of theories of sovereign default and provide a market-based estimate of sovereign default costs. We find that the stock prices of firms vulnerable to financial intermediation disruption, or firms more exposed to the government, are particularly sensitive to changes in sovereign credit spreads. This is consistent with theories in which default is costly because it disrupts financial intermediation and damages government reputation. Estimation of a structural valuation model indicates that the market prices stocks as if sovereign default has large effects on vulnerable stocks, translating to a 12% destruction of the value of their productive assets.